Age-related Metric Changes in Ear Size and Position - Sezgin, Nurdan; Ersoy, Gökhan (The Bulletin of Legal Medicine, 2020)
In this study, age changes in human face and ear were examined metric in both sexes. The data that have statistically significant results were included in the study, and we focused on the data with increase/decrease with age. In the study, measurements were made on the face profile and ear images of 369 volunteers (166 female and 203 male). Linear distance measurements were taken using 19 anthropometric points along with Body Mass Index (BMI), and face profile and ear area calculations. The data were recorded in SPSS 20.0 (Statistical Package fort he Social Sciences) and analyzed. Generally, the linear distance measurements taken from the ear region in both genders were observed to increase with age. While there was no statistically significant difference in the measurements taken on the side of the face, in men, only 4 of 13 measurements were observed to increase continuously. The aim of this study is to examine the changes in the human face profile and ear with age as a metric and to contribute to the future prediction studies.